Relationship between bacilloscopy and operational classification of Hansen's disease in patients with reactions - Marcel Alex Soares dos Santos; Larissa Mondadori Mercadante; Elisangela Samartin Pegas; Bogdana Victoria Kadunc (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Leprosy can be classified according to its operational form as paucibacillary or multibacillary. Bacilloscopy integrates its diagnostic armamentarium. Patients with the disease may present leprosy reactions. This study describes the association of bacilloscopy results and the type of operational classification of leprosy in patients with leprosy reactions. Medical records were analyzed at a reference center between 2010 and 2015. Reactions occurred in almost half of the patients, making their identification important. The bacilloscopic and operational characterization indicates a greater occurrence of leprosy reactions in patients with positive bacilloscopy and also in multibacillary.